2015
DOI: 10.1080/15592324.2015.1091909
|View full text |Cite
|
Sign up to set email alerts
|

Leaves may function as temperature sensors in the heterophylly of Rorippa aquatica (Brassicaceae)

Abstract: Many plants show heterophylly, which is variation in leaf form within a plant owing to environmental change. The molecular mechanisms underlying heterophylly have recently been investigated in several plant species. However, little is known about how plants exhibiting heterophylly sense environmental cues. Here, we used Rorippa aquatica (Brassicaceae), which shows heterophylly, to investigate whether a single leaf can sense and transit changes in ambient temperature. The morphology of newly developed leaves af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…For instance, exposing mature leaves to high concentrations of CO 2 or different light conditions was sufficient to reduce the opening and number of stomata in younger leaves ( Lake et al, 2001 ). Similarly, in the aquatic plant Rorippa aquatica (Lake cress) subjecting a single mature leaf to a temperature higher than the ambient temperature led to a decrease of the complexity of the margins in the newly developing leaves ( Nakayama and Kimura, 2015 ). During flooding, a long distance signal travels from the root to the shoot where it regulates leaf growth ( Jackson, 2002 ).…”
Section: Molecular Integration Of Environmental Signalsmentioning
confidence: 99%
“…For instance, exposing mature leaves to high concentrations of CO 2 or different light conditions was sufficient to reduce the opening and number of stomata in younger leaves ( Lake et al, 2001 ). Similarly, in the aquatic plant Rorippa aquatica (Lake cress) subjecting a single mature leaf to a temperature higher than the ambient temperature led to a decrease of the complexity of the margins in the newly developing leaves ( Nakayama and Kimura, 2015 ). During flooding, a long distance signal travels from the root to the shoot where it regulates leaf growth ( Jackson, 2002 ).…”
Section: Molecular Integration Of Environmental Signalsmentioning
confidence: 99%
“…Previous studies found that in some aquatic and amphibious plants, heteromorphic leaves evolved as a survival strategy, where the different relative positions to the water surface caused microenvironmental heterogeneity [2,8]. These heteromorphic leaves exhibit differences not only in leaf shape but also in morphological and physiology features [7]. In terrestrial plants, microenvironmental heterogeneity also exists, but it is not as obvious as that of aquatic and amphibious plants [1].…”
Section: Discussionmentioning
confidence: 99%
“…Microenvironmental changes may bring about variations of leaves, both in terms of morphology and physiology [7,33]. TATTINI et al demonstrated that trichomes are efficient at attenuating excess solar irradiance [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, GA may be utilized both of heterophylly and heteroblasty. Interestingly, a previous study showed that a single leaf can sense and transmit changes in ambient temperature to newly developed leaves in R. aquatica ( Nakayama and Kimura, 2015 ), suggesting that a long distance signal may be generated at a certain developmental stage of leaves. Transmembrane transport of GA in Arabidopsis is reported to be regulated by AtSWEET13, AtSWEET14, and AtNPF2.10/GTR proteins ( Kanno et al, 2016 ).…”
Section: How Do Gibberellins Regulate Heterophylly?mentioning
confidence: 99%